SURGICAL MANAGEMENT OF COMBINED RECTOCELE AND CYSTOURETHROCELE AND DETERMINANTS OF RECURRENCE - Navruzov, B.S.; Yusupov, Sh.B.; Rakhimov, O.U.; Sabirmatov, A.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2026)
Combined rectocele and cystourethrocele represent a frequent and therapeutically challenging form of pelvic floor dysfunction. Although numerous surgical techniques have been developed to address anterior and posterior compartment defects, long-term stability remains variable, and recurrence continues to be reported across different operative approaches. The coexistence of these conditions raises important questions regarding optimal surgical strategy, selection of access route, choice of reinforcement material, and adequacy of multilevel reconstruction. This narrative review analyzes contemporary evidence on native tissue repair, levatorplasty, mesh-augmented techniques, laparoscopic and robotic procedures, and combined reconstructive strategies in the management of rectocele associated with cystourethrocele. Particular attention is given to anatomical restoration versus functional outcome, predictors of surgical success, and factors associated with recurrence. Available data indicate that recurrence is influenced not only by technical execution but also by baseline pelvic floor integrity, multilevel involvement, connective tissue quality, and biomechanical load redistribution after repair. Comparative studies demonstrate that isolated compartment correction may lead to symptom persistence or progression in adjacent structures, while more extensive reconstructions do not uniformly translate into superior long-term outcomes. The evidence suggests that durability depends on balanced load distribution, appropriate patient selection, and integration of functional assessment into surgical decision-making. Understanding determinants of recurrence in combined rectocele and cystourethrocele is essential for refining operative strategy and improving long-term pelvic floor stability.